Leadership Development and Opportunities for Women in Higher Education Leadership Roles - Violon, James; Prado, Nenita (Journal of Interdisciplinary Perspectives, 2024)
This qualitative phenomenological study explores women's leadership development and opportunities at Central Mindanao University (CMU) in advanced leadership positions. It investigates the factors shaping their career trajectories, emphasizing the pivotal role of educational attainment, particularly doctoral degrees, in advancing women into leadership roles. The research highlights the importance of academic distinctions and a solid commitment to service as critical motivators for women to embrace leadership roles despite initial hesitations. The study delves into the expected behaviors and qualities of leaders in higher education, emphasizing attributes vital for fostering academic excellence and inclusivity. Utilizing a qualitative phenomenological approach, the research examines the lived experiences of women leaders at CMU. Semi-structured interviews with purposively selected women in leadership roles provide in-depth insights into their experiences, perspectives, and challenges. Thematic analysis reveals recurring patterns, themes, and nuances, offering a comprehensive understanding of women's leadership trajectories. Leadership roles present opportunities for both professional and personal development, yet biases and systemic barriers persist, perpetuating gender disparities. Environmental factors, such as organizational culture, significantly influence leadership behaviors, necessitating adaptive strategies. Institutional support systems, including mentorship initiatives, foster effective leadership. The diverse experiences of participants underscore the complexity of women's leadership journeys, offering valuable insights for aspiring leaders. Addressing biases, promoting equitable opportunities, and creating supportive environments can pave the way for gender equality at CMU and similar institutions. Embracing inclusive practices can empower CMU to champion gender diversity and equity in higher education.